Emergent Endovascular Treatment of Iatrogenous Pseudoaneurysms of the Neck Following Jugular Catheterization - Deniz, Sinan; Abaci, Gizem (Current Medical Imaging, 2024)
IntroductionInadvertent puncture of the adjacent structures during a central venous catheterization is a well-known complication which may be managed conservatively when the injury is self-limiting, but requires a further treatment when there’s a proof of an active bleeding and/or a growing hematoma.Case RepresentationWe report a case of a 57-year-old bone-marrow-transplant patient with neck hematoma and bleeding followed by a non-sonographic-guided central venous line placement. CT showed a right sided hematoma in the neck region with a midline shift of the airway. The patient was under prophylactic LMWH. Emergent angiography demonstrated three different bleeding sites which were successfully embolized with coil and liquid embolic agents by endovascular means.ConclusionInterventional radiology offers a quick and safe approach in the management of potentially life-threatening bleeding complications.
Keywords: Coils